Base‐Promoted Intramolecular Cyclization and Hydrolysis of 2‐(2‐Formylaryloxy)acetonitriles: An Efficient Domino to Approach Benzofuran‐2‐carboxamides. Issue 19 (18th May 2020) - A, Xue‐Jiao; Li, Xia; Liu, Bo; Huang, Guo‐Li
Abstract: A novel, efficient, and practical approach for the synthesis of benzofuran‐2‐carboxamides has been developed through the base‐promoted tandem intramolecular cyclization and hydrolysis of 2‐formylaryloxyacetonitriles at room temperature. This method provides a convenient route to benzofuran‐2‐carboxamides in up to 98% yield with favorable functional group compatibility. A gram‐scale reaction was also performed to demonstrate the scaled‐up applicability of this methodology. Abstract : Benzofuran‐2‐carboxamides have been synthesized in good to excellent yields via the base‐promoted tandem intramolecular cyclization and hydrolysis of 2‐(2‐formylaryloxy)acetonitriles at room temperature. An efficient and practical method provides a convenient route to benzofuran‐2‐carboxamides with favorable functional group compatibility. A gram‐scale reaction was also performed to demonstrate the scaled‐up applicability of this methodology.